LEAN AND GREEN SUPPLY CHAIN MANAGEMENT IN IMPROVING OPERATIONAL PERFORMANCE IN SUGAR INDUSTRY - Suhardini, Prasis Nursyam; Sudjatno, Sudjatno; Hadiwidjojo, Djumilah (Jurnal Aplikasi Manajemen, 2021)
The purpose of this study is to understand supply chain management practices, Lean & Green management, and the integration of Lean & Green Supply Chain Management in PG. Krebet Baru - PG. Rajawali I in improving operational performance in supplier and manufacturing chains. The method used is case study qualitative research through interviews, observation, documentation, document review & corporate websites that produce data analysis. The results of this research data analysis produced the first proposition related to supply chain management practices, namely coordination in the flow of material, information, and finance that is being increased by PG Krebet efforts in maintaining better cooperative relations with farmer groups as suppliers. The second proposition relates to lean management practices, namely the efficiency of human resources and natural resources, reduction of lead time, and reduction of inventory is an activity that can increase added value to the company. The third proposition is related to green management practices, namely environmentally-friendly innovation in the operating system is a strategy to improve the application of environmental management. The synergy between the practice of lean and green supply chain in improving operational performance also results in a fourth proposition, namely the commitment of suppliers (farmer groups) to PG. Krebet will improve company efficiency and environmental performance which may improve product quality and flexibility and reduce costs. Suggestions for further research, which in this case study, can be continued in the entire supply chain from suppliers to consumers to better understand lean and green management practices in all sugar industry supply chain members.